Pertumbuhan dan Struktur Umur Kerang Kepah (Meretrix meretrix) di Kampung Nipah Desa Sei Nagalawan Kecamatan Perbaungan Kabupaten Serdang Bedagai - Sakila, Nafi; Ramadhani, Dinda Ayu; Suryanti, Ani (Journal of Marine and Aquatic Sciences; Vol 4 No 2 (2018)DO - 10.24843/jmas.2018.v4.i02.316-323, 2017)
Sei Nipah has enormous potential for natural resources. Natural resources that serve as the main livelihood in fulfilling daily needs in Kampung Nipah is shellfish. Shellfish ( M. meretrix ) is one of the shells that many interested by the surrounding community. The purpose of this research is to know growth parameter and age group of shellfish ( M. meretrix ) in Kampung Nipah. The sampling technique was done randomly (simple random sampling). Sampling time is done at low tide. Sampling was conducted in March - May 2017. The results showed differences in the length of different shells each month. The size group of shellfish ( M. meretrix ) found only one size group during the three months of the study. Analysis of shellfish growth parameters based on data of long frequency distribution showed length of infiniti (L?) 33,10 mm and growth growth (K) that was 1,21 per month. Von Bertalanffy Growth Parameters Lt = 33.1 (1-e [-1.21 (t + 0.12)] ) Long infiniti size is seen the growth of shellfish shells can no longer be worked Shells reach maximum length at the age of 13 months with a shell length of 33.10 mm.The youthful shells have rapid growth and as age increases, when it reaches old age the rate of growth will slow even.